PENINGGALAN SARANA PERTAHANAN BELANDA PERANG DUNIA II DI TARAKAN - Susanto, Nugroho Nur (Naditira Widya, 2008)
However importing to power the oil Kalimantans special Tarakan island by Duck and frends in future. They are exploitations and want to defend. Voraciously Jepan for gulp down Tarakan island is very power. The evident of remaining World War II archaeologies: meriams, pillbox, bunker, battery, and war equipment in Tarakan still wa known is very clear. To looks the remaining World War II as thought is conscious the foreight want to commanded is Tarakan. Makes so realize we having in abundance.